Alternative fuels for transportation sector in Indonesia - Muji Setiyo (Universitas Muhammadiyah Magelang, 2022)
Only a few countries in the world have rich energy resources like Indonesia which owns practically all-natural energy resources, including biological resources. Japan, a country renowned for its technological advancements, lacks sufficient land to cultivate crops used as raw materials for biofuels. Several countries near the north pole, do not expose to sunlight throughout the year like Indonesia, which impacted to development of solar energy to provide electricity. Therefore, this short article reviews the three main energy sources available in Indonesia for the transportation sector, which include: natural gas and coal as new energy sources; natural energy for electricity and hydrogen supply, and energy from biological sources.